Proceedings of the 11th ACM Workshop on Hot Topics in Networks 2012
DOI: 10.1145/2390231.2390247
|View full text |Cite
|
Sign up to set email alerts
|

Towards systematic roadmaps for networked systems

Abstract: Networked systems have benefited from unprecedented growth in hardware capabilities, but, as we move closer to the end of the Moore's law era, future networked systems are likely to be more constrained by hardware capabilities than they have been in the past. We take the position that the networking community should, in response to this development, proactively and systematically develop networking roadmaps, which attempt to predict how trends in hardware capabilities will impact networked systems. In this pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…However, not all applications require such high hardware reliability. The authors in [5] have demonstrated that network applications can tolerate moderate failure rates in memories and function correctly with low performance degradations. This paper is one of our initial steps in characterizing the interplay of these solutions by considering clock period, test cost, yield, and failure rate to address the trade-off between the overall costs and benefits.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all applications require such high hardware reliability. The authors in [5] have demonstrated that network applications can tolerate moderate failure rates in memories and function correctly with low performance degradations. This paper is one of our initial steps in characterizing the interplay of these solutions by considering clock period, test cost, yield, and failure rate to address the trade-off between the overall costs and benefits.…”
Section: Introductionmentioning
confidence: 99%